Ембріологічні аспекти формування насіння Pinus sibirica Du Tоur в умовах Києва - Ruguzova, A.I.; Pokhylchenko, O.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
This article discusses some peculiarities of Pinus sibirica Du Tour reproduction cycle and seed productivity in the introduction conditions. Some morphometric parameters of reproductive structures and calendar terms for processes during the seed formation are given.